An R Package for Assessing Drug Synergism/Antagonism - John C. Boik (Journal of Statistical Software, 2010)
Synergistic and antagonistic drug interactions are important to consider when developing mixtures of anticancer or other types of drugs. Boik, Newman, and Boik (2008) proposed the MixLow method as an alternative to the Median-Effect method of Chou and Talalay (1984) for estimating drug interaction indices. One advantage of the MixLow method is that the nonlinear mixed-effects model used to estimate parameters of concentration-response curves can provide more accurate parameter estimates than the log linearization and least-squares analysis used in the Median-Effect method. This paper introduces the mixlow package in R, an implementation of the MixLow method. Results are reported for a small simulation study.